2013
DOI: 10.1111/acer.12056
|View full text |Cite
|
Sign up to set email alerts
|

Similar Ethanol Drinking in Adolescent and Adult C57BL/6J Mice After Chronic Ethanol Exposure and Withdrawal

Abstract: Background Increasing evidence shows that excessive alcohol consumption during adolescence increases vulnerability to alcohol use disorders in adulthood. The aim of this study was to examine differences between adolescent and adult C57BL/6 mice in drinking behavior and blood ethanol concentrations (BECs) after chronic ethanol exposure and withdrawal. Methods Male adolescent (PND=28–30) and adult (PND=70) C57BL/6J mice were allowed to consume ethanol in a two-bottle choice paradigm (15% ethanol vs. water) for… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

6
14
2

Year Published

2014
2014
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 17 publications
(22 citation statements)
references
References 52 publications
(78 reference statements)
6
14
2
Order By: Relevance
“…This withdrawal model used in this experiment has been successfully used in previous studies investigating the induction of physical dependence and withdrawal signs through abrupt cessation of binge ethanol intake (9–15 g/kg/day) for 3–4 days (Majchrowicz, 1975, Abulseoud et al, 2014). Withdrawal-induced escalation of ethanol drinking, observed in this study, is consistent with previous studies showing elevated ethanol drinking following intermittent ethanol exposure and/or withdrawal period (Carrara-Nascimento et al, 2013, Abulseoud et al, 2014). …”
Section: Discussionsupporting
confidence: 93%
“…This withdrawal model used in this experiment has been successfully used in previous studies investigating the induction of physical dependence and withdrawal signs through abrupt cessation of binge ethanol intake (9–15 g/kg/day) for 3–4 days (Majchrowicz, 1975, Abulseoud et al, 2014). Withdrawal-induced escalation of ethanol drinking, observed in this study, is consistent with previous studies showing elevated ethanol drinking following intermittent ethanol exposure and/or withdrawal period (Carrara-Nascimento et al, 2013, Abulseoud et al, 2014). …”
Section: Discussionsupporting
confidence: 93%
“…Previous work has described an array of neural and behavioral effects of CIE in male mice of several strains (though predominantly C57BL/6J) and various lines of male or sex-balanced groups of gene mutant mice (Becker, 2013). The reported behavioral effects of CIE in mice include elevated ethanol drinking (Becker & Lopez, 2004; Carrara-Nascimento, Lopez, Becker, Olive, & Camarini, 2013; Dhaher, Finn, Snelling, & Hitzemann, 2007; Finn et al, 2007; Griffin, Lopez, & Becker, 2009; Griffin, Lopez, Yanke, Middaugh, & Becker, 2009; Holmes et al, 2012; Lopez & Becker, 2005; McCool & Chappell, 2015), increased seizure susceptibility and anxiety-like behavior (Becker, 1994; Becker, Diaz-Granados, & Hale, 1997; Becker, Diaz-Granados, & Weathersby, 1997; Becker & Hale, 1993; Morales et al, 2015), tolerance to acute ethanol intoxication (Daut et al, 2015), and alterations in appetitive and aversive learning (DePoy et al, 2013, 2015; Holmes et al, 2012; Radke et al, 2015). In terms of sex differences, one study reported that male but not female HAP-2 mice showed increased ethanol drinking and withdrawal signs following CIE (Lopez et al, 2011).…”
Section: Introductionmentioning
confidence: 99%
“…Chronic intermittent ethanol vapor exposure (CIE) is a well-characterized mouse model of alcohol exposure that elicits an abstinence-induced escalation in voluntary ethanol consumption similar to that observed in human alcoholics (Becker, 2013; Becker and Lopez, 2004; Becker and Ron, 2014; Carrara-Nascimento et al, 2013; Crabbe et al, 2014; DePoy et al, 2013; Griffin, 2014; Griffin et al, 2009; Kissler et al, 2014; Lopez and Becker, 2005; Lopez et al, 2014; Repunte-Canonigo et al, 2014), as well as deficiencies in several other learned and affective behaviors, including attention set-shifting (Kroener et al, 2012), fear extinction (Holmes et al, 2012), reversal learning (Badanich et al, 2011), and anxiety and negative affect (Lowery-Gionta et al, 2014). These behaviors have been shown to be dependent on the PFC, CeA, and BNST, and withdrawal from CIE in mice produces alterations in several aspects of neural function in these regions.…”
Section: Introductionmentioning
confidence: 99%